Real-time reverse transcription loop-mediated isothermal amplification for rapid detection of yellow head virus in shrimp - Mekata, Tohru (J Virol Methods, 2009)
A real-time reverse transcription loop-mediated isothermal amplification (real-time RT-LAMP) method was applied for detecting the replicase polyprotein-encoding gene of yellow head virus (YHV) in shrimp, Penaeus monodon. It is a novel, gene-specific assay that amplifies nucleic acid with high specificity, sensitivity and rapidity under isothermal conditions using a set of six specially designed primers that recognize eight distinct sequences of the target gene. This method works with even low copies of DNA and is based on magnesium pyrophosphate turbidity detection by an inexpensive photometer for quantitative analysis. A user-friendly protocol was developed with optimal conditions standardized at 63 °C for 60 min. With this protocol, the assay sensitivity was 10 times higher than the widely used YHV nested RT-PCR system. Cross-reactivity analysis using other shrimp virus DNA/cDNA and YHV-negative shrimp demonstrated high specificity of the assay. The real-time RT-LAMP method was performed also for an internal control gene, EF-1α, to compare with the expressions of the YHV gene in different organs of infected shrimp, and the resulting standard curves showed high correlation coefficient values. These results suggest that this assay is applicable widely as a new quantitative detection method in the pursuit of YHV-free shrimp culture.